The Role of Risk Perception and Big Five Personality Traits in COVID-19 Vaccine Hesitancy in Indonesia - Zainurrahman, Muhammad Zaki Afif; Praptomojati, Ardian (Faculty of Psychology, Universitas Gadjah Mada, 2024)
Even when the COVID-19 global health emergency is declared over, vaccine hesitancy is a relevant topic that needs to be studied to ensure effective intervention when such cases arise again in the future. Vaccine hesitancy is a phenomenon of public doubt about whether to accept or reject vaccination. This study aims to determine the characteristics of vaccine hesitancy in Indonesian society and its relationship with the risk perception of COVID-19 and the Big Five personality traits. We also discuss how the present findings can inform future decision making on pandemic interventions. This multimethod cross-sectional study incorporated both quantitative and qualitative analyses through self-report measures and an open question. We distributed the questionnaire online through convenience sampling technique and involved 390 Indonesian citizens aged 18-62 years (Mage = 30.68, SD = +13.17). Through regression analyses, we found that risk perception of COVID-19, Extraversion, Conscientiousness, and Intellect were significant predictors of vaccine hesitancy. Thematic analysis showed that themes of lack of confidence, convenience, and complacency were present in participants’ attitudes toward COVID-19 vaccines. Demographic analysis also showed a correlation between vaccine hesitancy and economic status. Vaccination campaigns should focus on extensive education on vaccine safety that is backed by factual data, education on the risk of preventable diseases with vaccination, and increasing public confidence in government and health authorities.